Gambaran Kadar Protein Total pada Ibu Hamil di Wilayah Kerja Puskesmas Purnama, Kota Pontianak - Regita, Lidia; Nurhayati, Etiek; Tumpuk, Sri; Djohan, Herlinda (SENTRI: Jurnal Riset Ilmiah, 2025)
Maternal Mortality Rate is one of the indicators for assessing the quality of services place. In West Kalimantan Province, AKI is the highest serious concern, based on data that the local Health Office recorded about 432 cases of maternal deaths between 2022 and 2024. Preeclampsia, a severe pregnancy complication characterized by hypertension and proteinuria, has been identified as a major cause of this mortality. Early detection of proteinuria, which can be done through a simple urine test, is a key strategy for risk mitigation. This study aims to determine the prevalence of proteinuria levels among pregnant women in the working area of the Purnama Community Health Center, Pontianak City, as part of an effort for early detection. The research method used is a quantitative descriptive study with a case study approach, involving 30 pregnant women as samples. The examination was performed using the urine dipstick method. Demographic data, specifically age and blood type, as well as the proteinuria test results, were analyzed descriptively to identify their frequency and percentage. The study's results show that out of the 30 samples, 13 (43.3%) tested positive for proteinuria, with a breakdown of 7 samples showing trace positive (+ Protein), 4 samples showing positive (Pro 1 (+)), and 2 samples showing positive (Pro 2 (+)). These findings confirm a significant prevalence of preeclampsia risk among the sample population and underscore the importance of routine screening programs and further clinical evaluation for pregnant women who test positive.